Accelerating CO2 Electroreduction to CO Over Pd Single‐Atom Catalyst. (1st March 2020) - He, Qun; Lee, Ji Hoon; Liu, Daobin; Liu, Yumeng; Lin, Zhexi; Xie, Zhenhua; Hwang, Sooyeon; Kattel, Shyam; Song, Li; Chen, Jingguang G.
Abstract: The electrochemical conversion of carbon dioxide (CO2 ) into value‐added chemicals is regarded as one of the promising routes to mitigate CO2 emission. A nitrogen‐doped carbon‐supported palladium (Pd) single‐atom catalyst that can catalyze CO2 into CO with far higher mass activity than its Pd nanoparticle counterpart, for example, 373.0 and 28.5 mA mg −1 Pd, respectively, at −0.8 V versus reversible hydrogen electrode, is reported. A combination of in situ X‐ray characterization and density functional theory (DFT) calculation reveals that the PdN4 site is the most likely active center for CO production without the formation of palladium hydride (PdH), which is essential for typical Pd nanoparticle catalysts. Furthermore, the well‐dispersed PdN4 single‐atom site facilitates the stabilization of the adsorbed CO2 intermediate, thereby enhancing electrocatalytic CO2 reduction capability at low overpotentials. This work provides important insights into the structure‐activity relationship for single‐atom based electrocatalysts. Abstract : A palladium (Pd)‐based single‐atom catalyst with PdN4 sites is identified as an efficient electrochemical CO2 reduction reaction (CO2 RR) catalyst. It is capable of converting CO2 into CO without the Pd hydride formation essential for typical bulk Pd‐based catalysts. This study reveals the comprehensive structure–activity relationship for the isolated and bulk Pd catalysts in electrochemical CO2 RR.